Relación entre la recaudación tributaria y el control interno en la Municipalidad de Punchana durante el periodo 2025 - Panduro Vela, Renzo Arturo (2025)
The present research aimed to analyze the relationship between tax collection and internal control in the Municipality of Punchana during the year 2025. The study followed a quantitative approach, with a correlational scope and a non experimental design, applying surveys to 97 administrative workers directly involved in tax management. Statistical techniques were employed for data analysis, with Spearman’s correlation as the main tool to validate the proposed hypotheses. The results revealed a positive and significant relationship between internal control and tax collection (Rho=0.7011; p=0.0262), confirming that an efficient internal control system strengthens tax collection management. Moreover, a very strong relationship was found between collection efficiency and the control environment (Rho=0.9365; p=0.0288), as well as between the amount of local taxes collected and risk assessment efficiency (Rho=0.8153; p=0.0385). These findings are consistent with previous studies that emphasize the importance of transparency, institutional coordination, and risk management as key factors for the sustainability of municipal revenues. In conclusion, this research demonstrates that internal control not only significantly influences tax collection but also constitutes a fundamental pillar to ensure efficiency, equity, and fiscal sustainability in local governments.